DFT calculations of KI crystals formed within single-walled carbon nanotubes - Sceats, E; Green, M; Kirkland, A; Green, J (2008)
Density functional theory calculations are used to obtain structures for KI crystals formed within single-walled carbon nanotubes. The predicted structures are compared with experimental specimen exit plane wavefunctions restored from focal series of high-resolution electron microscope images. These comparisons show good agreement between the calculated structure for KI@(12,12). The calculations also predict that surface rumples invert as the crystal becomes more compressed. © 2008 Elsevier B.V. All rights reserved.